A complete assessment of tagging quality: A consolidated methodology - Choi, Yunseon (Association for Information Science and Technology, 2015)
This paper presents a methodological discussion of a study of tagging quality in subject indexing. The data analysis in the study was divided into 3 phases: analysis of indexing consistency, analysis of tagging effectiveness, and analysis of the semantic values of tags. To analyze indexing consistency, this study employed the vector space model-based indexing consistency measures. An analysis of tagging effectiveness with tagging exhaustivity and tag specificity was conducted to ameliorate the drawbacks of consistency analysis based on only the quantitative measures of vocabulary matching. To further investigate the semantic values of tags at various levels of specificity, a latent semantic analysis (LSA) was conducted. To test statistical significance for the relation between tag specificity and semantic quality, correlation analysis was conducted. This research demonstrates the potential of tags for web document indexing with a complete assessment of tagging quality and provides a basis for further study of the strengths and limitations of tagging.
Keywords: Consistency analysis; Consistency measures; Correlation analysis; Indexing (of information); Information retrieval; Latent Semantic Analysis; Organization of informations; Quality control; Quantitative measures; Semantics; Statistical significance; Subject indexing; Vector spaces; clinical trial; correlation analysis; data analysis; dept.ils; human; information retrieval; linguistics; model; organization of information; quantitative study; statistical significance; subject indexing